Serum salusin-? and salusin-? levels in patients with Behcet's disease - Erden, Ilker; Demir, Betul; Ucak, Haydar; Cicek, Demet; Dertlioglu, Selma Bakar; Aydin, Suleyman (John Libbey Eurotext Ltd, 2014)
Background: Behcet' s disease (BD) is a chronic, relapsing, systemic vasculitis of unknown etiology. There is an increased predisposition to insulin resistance and metabolic syndrome (MetS) in BD patients. Objective: The aim of this study was to determine serum salusin-alpha and salusin-beta levels in BD patients and healthy controls and to investigate their association with MetS. Patients and Methods: Twenty-five BD patients and 25 healthy controls were included in the study. Salusin-alpha and salusin-beta levels were measured in blood samples using ELISA. In addition, BD patients and healthy controls were evaluated in terms of MetS. Results: The mean serum salusin-alpha level in BD patients was significantly lower compared to healthy controls (p = 0.03), whereas the mean serum salusin-beta level in BD patients was significantly higher compared to healthy controls (p = 0.03). The mean serum salusin-alpha level was significantly lower in BD patients with MetS compared to BD patients without MetS (p = 0.04). Conclusions: Serum salusin-a level (an anti-atherogenic molecule) was lower, while serum salusin-beta level (a pro-atherogenic molecule) was higher in BD patients. We consider that the decrease in salusin-alpha and the increase in salusin-beta levels contribute to the development of MetS.
Keywords: Behcet's Disease; salusin-alpha; salusin-beta; metabolic syndrome; insulin resistance